Surgical outcomes after radioactive 125I seed versus hookwire localization of non-palpable breast cancer: a multicentre randomized clinical trial. Issue 1 (23rd December 2020) - Taylor, D B; Bourke, A G; Westcott, E J; Marinovich, M L; Chong, C Y L; Liang, R; Hughes, R L; Elder, E; Saunders, C M
Abstract: Background: Previous studies have suggested improved efficiency and patient outcomes with 125 I seed compared with hookwire localization (HWL) in breast-conserving surgery, but high-level evidence of superior surgical outcomes is lacking. The aim of this multicentre pragmatic RCT was to compare re-excision and positive margin rates after localization using 125 I seed or hookwire in women with non-palpable breast cancer. Methods: Between September 2013 and March 2018, women with non-palpable breast cancer eligible for breast-conserving surgery were assigned randomly to preoperative localization using 125 I seeds or hookwires. Randomization was stratified by lesion type (pure ductal carcinoma in situ (DCIS) or other) and study site. Primary endpoints were rates of re-excision and margin positivity. Secondary endpoints were resection volumes and weights. Results: A total of 690 women were randomized at eight sites; 659 women remained after withdrawal ( 125 I seed, 327; HWL, 332). Mean age was 60.3 years in the 125 I seed group and 60.7 years in the HWL group, with no difference between the groups in preoperative lesion size (mean 13.2 mm). Lesions were pure DCIS in 25.9 per cent. The most common radiological lesion types were masses (46.9 per cent) and calcifications (28.2 per cent). The localization modality was ultrasonography in 65.5 per cent and mammography in 33.7 per cent. The re-excision rate after 125 I seed localization was significantly lower than for HWL (13.9 versus 18.9 per cent respectively; P  = 0.019). There were no significant differences in positive margin rates, or in specimen weights and volumes. Conclusion: Re-excision rates after breast-conserving surgery were significantly lower after 125 I seed localization compared with HWL. Registration number: ACTRN12613000655741 (http://www.ANZCTR.org.au/ ). Abstract : This is the first study to confirm a significant improvement in re-excision rate for breast conserving surgery (BCS) using radioactive seed rather than hookwire guidance. 659 patients were randomised to undergo BCS with iodine125 seed or hookwire localisation. Re-excision rates were significantly lower in the seed group. Involved margin rates were also lower, although this did not reach statistical significance. BCS with radioactive seed rather than wire guidance does give superior patient outcomes.